THE LOGIC OF COSMOPOLITANISM AND THE IDEA OF INTERNATIONAL JUSTICE - Isenyo Solomon Ogaba (Universitas Negeri Makassar, 2021)
Cosmopolitanism considers the citizens of states as citizens of the world. In this way, cosmopolitanism transcends the idea of the state. The question then is, can cosmopolitanism offer a conceptual grid from where to begin to theorize the possibility of principles of international justice? Does cosmopolitanism carry a credible understanding of the relationship between the self and the other which could inform a viable and valid conception of justice for states? Does the cosmopolitan perspective contain the basis for international justice? In a world constitutive of cosmopolitan individual citizens, what constitutes and represents our agency, choice and consensus? Which of us would be responsible for working out the appropriate understanding of justice and its applicability? By merely labelling all individuals as citizens of the world, it does not offer an adequate or compelling account of the mechanisms of enforceability? And finally, and perhaps most importantly, who is the other in a cosmopolitan world? These and many more are questions in which this work tends to shed light on. This work points that, in a world divided by nation states, this seems somewhat impractical as well as undesirable. This work argues that cosmopolitan account does offer a convincing moral perspective, it fails almost entirely in offering a compelling political narrative.